Mentalization Episodes During Psychotherapy in Adolescents with Identity Diffusion - Quevedo, Yamil; Hernández, Cristóbal; Gómez, Diana; Díaz, Carmen Gloria; Valdés, Nelson (Revista de Psicología, 2019)
Identity diffusion is considered a central element in the psychopathology of borderline personality disorder, which is rooted in deficits in mentalization skills. This article presents the results of a qualitative analysis carried out on the patients’ and therapists’ narratives during psychotherapeutic sessions with the Identity Treatment for Adolescents model (AIT), in which adolescents were diagnosed with an identity diffusion. The findings allowed to propose a new way for identifying, delimiting and describing mentalization episodes within the psychotherapeutic dialogue. A description of these relevant episodes is presented, depending on their level of complexity, their proximity to the patient’s biographical-affective history, and the focus placed on him/herself or others. Such episodes were usually pre-ceded by certain actions from therapists, which can facilitate or attenuate the patient’s mentalization processes. These results are discussed considering their potential to guide clinical practice, the training of therapists, and the conduct of future research.